2011
DOI: 10.1111/j.1349-7006.2011.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

CpG island methylation of microRNAs is associated with tumor size and recurrence of non‐small‐cell lung cancer

Abstract: We investigated whether the CpG island methylation of certain microRNAs was associated with the clinicopathological features and the prognosis of non-small-cell lung cancer. The methylation of mir-152, -9-3, -124-1, -124-2, and -124-3 was analyzed in 96 nonsmall-cell lung cancer specimens using a combined bisulfite restriction analysis. The median observation period was 49.5 months. The methylation of mir-9-3, -124-2, and -124-3 was individually associated with an advanced T factor independent of age, sex, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…Following a bioinformatic search for candidate CpG islands 5= of miRNA genes, it was initially shown that the mir-9-1 gene was hypermethylated in primary invasive breast tumors (22). Additional studies have since shown that mir-9 loci are epigenetically silenced in gastric tumors (9), breast mammosphere models (23), oral squamous cell carcinoma (24), and non-small-cell lung cancers, where methylation of mir-9-3 can serve as a prognostic indicator (25,26). To see if methylation was a contributing silencing mechanism in our system, we first treated cells with the methyltransferase inhibitor 5-aza-2=-deoxycytidine (5AZA).…”
Section: Resultsmentioning
confidence: 99%
“…Following a bioinformatic search for candidate CpG islands 5= of miRNA genes, it was initially shown that the mir-9-1 gene was hypermethylated in primary invasive breast tumors (22). Additional studies have since shown that mir-9 loci are epigenetically silenced in gastric tumors (9), breast mammosphere models (23), oral squamous cell carcinoma (24), and non-small-cell lung cancers, where methylation of mir-9-3 can serve as a prognostic indicator (25,26). To see if methylation was a contributing silencing mechanism in our system, we first treated cells with the methyltransferase inhibitor 5-aza-2=-deoxycytidine (5AZA).…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of certain miRNAs in NSCLCs was also investigated in the studies by Kitano and colleagues (44) and by Watanabe and colleagues (23). Kitano and colleagues (44) observed miR-9-3 methylation in 65% of primary NSCLCs.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation statuses of miR-124-2 and miR-124-3 were individually related to recurrence of NSCLC. 78 Tan et al 86 conducted research on the NSCLC tumor samples and found higher amount of methylated miR-124a, especially miR-124a-2 and 124a-3, in tumors compared with normal lung tissues.…”
Section: Mir-148amentioning
confidence: 99%
“…In the human genome, miR-9 is located at three distinct loci: miR-9-1/2/3. So, except miR-9-2, all of them have CpG islands; 78 In all normal tissues, miR-9 family was always unmethylated. Lujambio et al 74 treated metastatic cancer cell lines with the DNMT inhibitor 5-aza-2′-deoxycytidine and measured the miRNA expression.…”
Section: Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation